2015
DOI: 10.1007/s00249-015-1050-9
|View full text |Cite
|
Sign up to set email alerts
|

C60 fullerene affects elastic properties and osmoregulation reactions of human lymphocytes

Abstract: The influence of aqueous solution of pristine C60 fullerene (C60FAS) on functional activity of lymphocytes from a healthy person was studied for the first time. By means of atomic force microscopy, it was found that C60FAS in a concentration of 0.1 mg/ml increases the stiffness of the lymphocyte membrane by 41% (p < 0.05) and lowers the functional activity of the plasmalemma surface, thereby constraining the use of its membrane material in physiological reactions using a hypotonic model in vitro. However, a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The absence of specific peculiarities on the curve suggests that the particles are polydisperse in size. It is in a good agreement with probe microscopy data [40, 41]. At sufficiently small q values ( qR g  < 1), the scattered intensity can be described by the Guinier approximation
Fig.
…”
Section: Resultssupporting
confidence: 88%
“…The absence of specific peculiarities on the curve suggests that the particles are polydisperse in size. It is in a good agreement with probe microscopy data [40, 41]. At sufficiently small q values ( qR g  < 1), the scattered intensity can be described by the Guinier approximation
Fig.
…”
Section: Resultssupporting
confidence: 88%
“…Unmodified bucky balls are hydrophobic rendering them poorly soluble in aqueous media, and interesting fundamental studies show that they interact with amphiphilic cell membranes prior to uptake [22][23][24][25], they are relatively quickly cleared from blood (accumulating in the liver and spleen [25]), and they exhibit dose-dependent toxicity in vivo (low toxicity at low concentrations in mice, and high toxicity at high concentrations with potential for mutagenic/teratogenic activity) [25].…”
Section: Bucky Ballsmentioning
confidence: 99%
“…[30] Meanwhile, Skorkina et al found that the aqueous solution with the C 60 concentration of 0.1 mg/ml can increase the stiffness of the lymphocyte membrane by 41%. [31] In addition, Zhou et al revealed that the incorporation of C 60 with a molar concentration of 0.8% can increase Young's modulus of gel phase lipid bilayers, but barely changes that of fluid phase bilayers. [32] On the other hand, molecular dynamics (MD) simulations showed that C 60 molecules are capable of translocating to the internal region of lipid bilayers spontaneously, affecting the structures and mechanic properties of plane membranes as well as inducing the dynamic interactions.…”
Section: Introductionmentioning
confidence: 99%